EARLY SOCIO-PHILOSOPHICAL VIEWS OF CENTRAL ASIAN THINKERS ON CIVIL SOCIETY (Scientific journal of the Fergana State University, 2023)
The article aims to research the emergence and historical evolution of ideas and views on civil society in Central Asia in a socio-philosophical way. The authors tried to substantiate the ijtimi-political views of the great ancient scholars of Central Asia, including: Abu Nasr Farabi, Ibn Sina, Alisher Navoi and state and public figures Amir Temur, on the need for today's study.